Self-healing materials for flexible electronic devices - Tiwari, Naveen (Nanyang Technological University, 2020)
With the onset of flexible and wearable electronics, devices are now put on places like the human body and various curved surfaces which doesn’t have any regular shape and sizes. Therefore, these devices need to be flexible, conformable and stretchable to fulfil all these applications. However, the continuous exposure of these devices is always subjected to higher mechanical stress, wear and tear when compared to conventional electronics. Hence the ability to recover and repair upon damage is a necessity and not a luxury for flexible electronic devices. These applications not only require good electrical conductivity but demand better mechanical properties like stretchability, flexibility and robustness where the conventional electrodes, for example, indium tin oxide (ITO) fail to perform. Hence, self-healing, flexible, transparent electrodes could transform the way of fabrication of electronic devices in future. Challenges associated with mechanical fracture of electrical conductors has hindered the realization of truly flexible, robust and high-performance wearable electronics. The remarkable achievements in transparent and flexible electrodes have raised widespread interest in research groups in flexible electronics, owing to their low-cost fabrication, easy scale-up, and unique properties. However, they still suffer from innate problems like mechanical rupture, scratching and bending torsion because of their “soft” and flexible nature related to their solid counterparts. Hence, self-healing capability would be highly desirable for these electrodes in flexible electronic devices. In this dissertation, the demonstration of versatile transparent healable electrodes has been developed and examined to alleviate these problems. The composite electrode features a layer of interconnecting AgNWs network on a polyurethane film modified with Diels–Alder adducts (PU-DA). The PU based DA polymeric electrode can heal multiple times due to the presence of DA and retro-DA mechanism, which are based on thermo-reversibility. Surface modification using hydrophilic molecules improved adhesion of the AgNWs and resulted in mechanically robust flexible electrodes with a high figure of merit; showing low sheet resistance with good transmittance in the visible spectrum. Transparent and flexible healable heaters (TFHH) with good mechanical and thermal stability were fabricated using these electrodes for potential applications in thermochromics, electrically driven displays and defrosters. The PU-DA based healable heaters exhibited high Joule heating temperatures with a low operation voltage, rapid thermal response and enhanced robustness to withstand large repeated mechanical strain for over 500 bending cycles with small variance in resistance. After deliberate damage by a knife cut, the electrodes healed and recovered back to its original conductivity via a simple heat treatment at 120 °C. Uniquely, the healing process can also be triggered by utilizing electrical power. The self-healing polymer with the addition of ionic liquids (ILs) may have great potential for future electronic materials. ILs would make it possible to integrate functional excipients to recognize multifunctional electrical applications; owing to the intrinsic advantages of suppressed volatility, high ionic mobility, thermal stability, and a wide range of electrochemical window. Thermally-reversible Diels-Alder (DA) mechanism for self-healing are promising but have only been demonstrated healing at high temperatures (~120 °C). However, theoretically, the DA mechanism can be triggered at temperatures as low as 50 °C, indicating that the self-healing mechanism is limited by the thermal mobility of the polymeric chains. Next, the effect of ionic liquid as a plasticizer was investigated in PU-DA in order to minimize the healing temperature and increase the mechanical properties of the polymeric composite. The incorporation of ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMITFS) alleviates this challenge, rapidly accelerating healing, while concomitantly improving the dielectric constant and the mechanical properties of a polyurethane derivative based on the DA chemistry for PU. For optimized compositions, the healing temperature reduced from 120 °C to 60 °C and the maximum strain to failure significantly increased from 17.1% to 102.1%. Owing to the ionic polarizability of EMITFS, the composite exhibited highly attractive dielectric properties with the dielectric constant enhanced from 2.7 to 12.9. Finally, a highly flexible, healable and fully solution-processed electroluminescent device was demonstrated. To tailor specific multi-property materials, usually, sophisticated multi-step synthesis processes are employed and will affect the device fabrication method. With the increase in concertation of ionic liquid, the polymeric films have increased in mechanical, electrical as well as healing properties as it was observed in the case of PU-DA. Taking that concept as a motivation, a composite system with healing behaviours in polymeric systems without DA recovery mechanism was investigated. The incorporation of ionic liquid (EMITFS) in amorphous polymer like PVP, rapidly accelerates the healing, while improving the mechanical properties. The PVP with ILs composite films were compared with IL composites with another amorphous polymer, PMMA, as well as semi-crystalline polymers like PVA and PVDF-HFP to mimic the healing behaviours and mechanical properties, while incorporating EMITFS in these polymers. The effect of cation and anion present in ionic liquids was investigated, on the best polymer system (PVP), in terms of healing behaviour and mechanical properties. The different ionic liquids (EMITFB and EMITFSI) was used as compared to EMITFS since these ionic liquids have the same cation but different anions. This chapter depicts the study of the influence of ionic liquids on the different class of polymer structure and its effects on the healing properties. In the end, a novel healing mechanism with ionic liquids was demonstrated in PVP polymer without DA recovery mechanisms.